In her name [videorecording (DVD)] - Garenq, Vincent; Garenq, Vincent; Auteuil, Daniel; Koch, Sebastian, 1962-; Croze, Marie-Josée, 1970- (Icarus Films Home Video, 2018)
After he learns that his fourteen-year-old daughter has died on vacation with her mother and stepfather, a man becomes convinced that she was murdered and sets out on a decades-long quest to prove his suspicions.